2015
DOI: 10.1186/s40463-015-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Face and content validity of a novel, web-based otoscopy simulator for medical education

Abstract: BackgroundDespite the fact that otoscopy is a widely used and taught diagnostic tool during medical training, errors in diagnosis are common. Physical otoscopy simulators have high fidelity, but they can be expensive and only a limited number of students can use them at a given time.Objectives1) To develop a purely web-based otoscopy simulator that can easily be distributed to students over the internet. 2) To assess face and content validity of the simulator by surveying experts in otoscopy.MethodsAn otoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Whether to aid with tympanic membrane visualization using image capture of the tympanic membrane or for skills-training with simulation, advances should be explored in the context of improving diagnostic accuracy in the clinical settings. 15 However, it should be noted that under resourced clinics may nd it challenging to implement such emerging technology.…”
Section: Discussionmentioning
confidence: 99%
“…Whether to aid with tympanic membrane visualization using image capture of the tympanic membrane or for skills-training with simulation, advances should be explored in the context of improving diagnostic accuracy in the clinical settings. 15 However, it should be noted that under resourced clinics may nd it challenging to implement such emerging technology.…”
Section: Discussionmentioning
confidence: 99%
“…Other nursing education work has posited that there is no difference between gamified learning versus face-to-face clinical simulation [43]. Medical education research has found largely positive results regarding the use of gamification as a teaching-learning mechanism, in terms of medical content validity [27], acceptance of and retention of learned knowledge [44], and ongoing skill retention and learner engagement [29,45]. The growing importance and interest in this topic can also be inferred from the recent registration of a Cochrane Database of Systematic Review protocol, which plans to examine the effectiveness of serious gaming and other gamified interventions in health professional education [38].…”
Section: Discussionmentioning
confidence: 99%
“…To assist with game development of the eMAR simulator, the research team partnered with a videogame company (Mikutech, Joydrop Ltd. London, Canada) that has significant experience in the areas of videogame and software development, including the specialized fields of education, engineering, and healthcare [27]. Drawing on previous research and medication administration workflow on the SMART eMAR [11,24], two main teaching-learning directions were targeted in the eMAR simulator game development.…”
Section: Planned Gamificationmentioning
confidence: 99%
“…These models consisted of 21 synthetic, 12 computer-based, 2 animal cadaver, and 2 human cadaver models. All computer-based models utilized virtual reality (VR) technology except for one web-based otoscopy simulator aimed for otoscopic examination described by Wickens et al [11]. Of these 37 models, 13 were intended for temporal bone drilling (35%), 11 were aimed for ventilation tube insertion (30%), and others included a variety of other ear surgical procedures.…”
Section: Otologymentioning
confidence: 99%